Blanca Varela: una poeta vestida de humana - Modesta Suárez (Caravelle)
Blanca Varela (1926-2008), «human dressed poet», is one of the mayor voices of contemporary Latin American poetry. When we consider her writing –writing of desire and disaster−, we discover a lyrical subject impressed by the Surrealist artists’ universe in its pictorial aspect. It can also enable to question some tensions, among which, the one emerging from the meeting of the poetical figure with the animal one. The permanent inclusion of thought concerning the animal component permits Blanca Varela to consider human evolution, one of the main interrogations of contemporary poetry.